Media and information literacy in the age of surveillance capitalism - Riva Casas, Andrés (Universidad Centro Latinoamericano de Economía Humana (Universidad CLAEH), 2019)
All over the world, democratic systems are facing the radical change of the new ways of citizenship. This is explained by technological advancements and, mainly, by the emergence of a new virtual public space in which game rules are completely different. By introducing the concept of surveillance capitalism, this paper seeks to draw attention to the threats and challenges presented by technological change, while proposing an approach from the educational system, integrating media and information literacy as a civic training to exercise citizens’ rights and freedoms in the new virtual space.